Construction of a peri-urban space typology for La Plata district (Argentina) - Frediani, Julieta Constanza (2009)
The objective of this paper is to build a typology of the peri-urban areas of La Plata District that allows us to characterize the diversity of these dynamic areas and to recognize differences and similarities within themselves. The typology proposed is aimed at contributing to the knowledge of periurban areas through the simplification of the phenomenon, establishing types or categories that serve as bench marks for the explanation of it. Also, the construction of this typology contributes to the development of a replicable methodology for the analysis of these spaces in other mid-sized cities.